The Influence of Covid-19 Daily Cases, World Oil Prices, World Gold Prices And Rupiah Exchange Rates - Achmad Agus Priyono (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study aims to clarify the effect of the daily number of reported cases of Covid-19, World Oil Prices, World Gold Prices, and the rupiah exchange rate on the movement of the Composite Stock Price Index during the Covid-19 Pandemic, both in the short and long-term. Analysis of the data used is the analysis of Error Correction Mechanism using Eviews software. The data collected is daily time series data from March 2, 2020 to July 30, 2021, so the number of samples collected is 341 samples. The results of the study stated that the increase of daily reported Covid-19 cases had a negative impact on the movement of the Composite Stock Price Index in the short term, however, in the long-term, the increase of daily reported cases of Covid-19 has no effect on the Composite Stock Price Index. Meanwhile, World Oil Prices have a significant positive effect on the Composite Stock Price Index both in the short term and in the long-term. This study did not find any short-term or long-term effect between the World Gold Price on the movement of the Composite Stock Price Index. A significant negative effect was found, both in the short term and in the long-term, in the relationship between the Rupiah Exchange Rate on the movement of the Composite Stock Price Index.